A squeeze and excitation ResNeXt-based deep learning model for Bangla handwritten basic to compound character recognition - Khan, Mohammad Meraj (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science and Engineering, 2021.